Short-term inhalation of cadmium oxide nanoparticles alters pulmonary dynamics associated with lung injury, inflammation, and repair in a mouse model. (January 2014) - Blum, Jason L.; Rosenblum, Lauren K.; Grunig, Gabriele; Beasley, Mary Beth; Xiong, Judy Q.; Zelikoff, Judith T.
Abstract Context: Cadmium oxide nanoparticles (CdO NPs) are employed in optoelectronic devices and as a starting material for generating quantum dots as well as for medical imaging and targeting of pharmaceutical agents to disease sites. However, there are lack of data concerning short- and long-term effects of CdO NPs on the lungs. Objective: To determine the effects of inhaled CdO NPs at an occupationally relevant concentration on pulmonary injury and repair, and on systemic immunity in adult male mice. Methods: Mice were exposed to 240 μg CdO NPs/m3 for seven days (3 h/d) and lavage levels of pulmonary injury/inflammatory markers, bacterial uptake by circulating phagocytes, and lung histology examined either one or seven days following the final exposure. Results: Levels of total protein, lactate dehydrogenase activity, cytokine markers of inflammation (i.e. interleukin-1β, tumor necrosis factor-α, and interferon-γ), tissue remodeling matrix metalloproteinases (MMP)-2 and -9 activity, and phagocytic activity of circulating phagocytes were significantly increased one day after the final exposure. By seven days post-exposure, MMP-2 activity decreased to control levels, while MMP-9 activity remained significantly above control values, although dropping by about half from day one. Conclusions: This study demonstrates that short-term inhalation exposure to CdO NPs can stimulate pathways in the lungs associated with inflammation, cell injury, and tissue remodeling as well as alter immune function. Findings here demonstrate that even short-term inhalation exposure to CdO NPs in the workplace could lead to deleterious pulmonary effects in exposed workers.